Carbon dioxide adsorption mineralization material as well as preparation method and application thereof

Through the hydrothermal reaction between silicon source and calcium source in an alkaline environment, materials that integrate carbon dioxide adsorption and mineralization functions are prepared, solving the high cost problem in distributed carbon emission scenarios, and achieving low-energy consumption carbon dioxide capture and Mineralization and promote crop yield increase, reducing overall carbon sequestration costs.

CN119186480APending Publication Date: 2024-12-27CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310752864.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing carbon dioxide capture and storage technology is costly in distributed carbon emission scenarios, and the preparation procedures for traditional adsorbents and mineralizers are cumbersome and energy consumption is high, making it difficult to achieve economically feasible deployment of negative carbon technology.

Method used

The silicon source and calcium source are used to carry out hydrothermal reaction in an alkaline environment to prepare a material integrating carbon dioxide adsorption and mineralization functions, simplify the process, reduce costs, and achieve carbon dioxide capture and mineralization under natural conditions. No harsh conditions are required.

Benefits of technology

Low-cost, low-energy consumption carbon dioxide adsorption and mineralization can efficiently capture and mineralize carbon dioxide under natural conditions, and act as a soil conditioner to promote crop yield and reduce overall carbon sequestration costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186480A_ABST
    Figure CN119186480A_ABST
Patent Text Reader

Abstract

According to the carbon dioxide adsorption and mineralization material and the preparation method and application thereof, the carbon dioxide adsorption and mineralization material prepared on the basis of the method is simple in preparation process and low in cost, the obtained material integrates carbon dioxide adsorption and mineralization functions, and adsorption and mineralization of carbon dioxide can be achieved without harsh conditions; in addition, when the carbon sequestration agent is applied to soil where crops grow, the carbon sequestration of the crops can be synchronously carried out, and the yield increase of the crops is promoted. The preparation method of the carbon dioxide adsorption and mineralization material mainly comprises the following steps: carrying out a hydrothermal reaction on a first material and a second material in an alkaline environment at 90-120 DEG C, filtering and washing the obtained product, and optionally drying to obtain the carbon dioxide adsorption and mineralization material, wherein the first material is a silicon source, and the second material is a calcium source; the first material and the second material are fed according to the molar ratio of Si to Ca of 1: (0.6-1.5).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dioxide capture and storage, and in particular to a carbon dioxide adsorption and mineralization integrated material and a preparation method and application thereof. Background Art

[0002] Carbon dioxide capture and storage (CCS) is the most direct and effective way to achieve "negative carbon". It is imperative to carry out CCS research and industrial practice. Different from the "centralized carbon emissions" of coal-fired power plants, "distributed carbon emissions" such as land transportation, aviation, industrial enterprises, and residents' heating coal and gas account for about 50% of the total carbon emissions. For this considerable amount of distributed carbon emissions, the current mainstream centralized fixed-point CCS technology is not applicable. In the traditional CCS system, the CO2 capture link alone accounts for as much as 70% of the total cost; and for distributed carbon emissions, the cost of CO2 capture with existing technology will increase exponentially, making the entire system completely uneconomical.

[0003] The industry has proposed the idea of ​​directly capturing carbon dioxide from the air (Direct Air Carbon Capture, DAC). The advantage of DAC is that it can be "distributed" arranged, for example, it can get rid of the geographical location restrictions of the "carbon source" and be built in areas close to non-carbon, low-cost energy such as wind power and solar energy, and the scale can be large or small. However, the industry currently still tends to use organic amine adsorbents with high adsorption performance but high cost, and relies on electric energy to drive a large amount of air to fully contact the adsorbent so that the dilute carbon dioxide (350ppm) in it can be adsorbed and separated; carbon dioxide desorption and adsorbent regeneration processes also require higher energy and some adsorbent loss. The above aspects mean higher raw material costs and energy consumption costs. It is estimated that the current cost of fixing 1t of carbon dioxide by direct air capture and storage of carbon dioxide (DACCS) is between US$200 and US$1,000; cost is still the core factor restricting the development of DACCS technology, and finding low-cost, high-adsorption adsorbents is the key.

[0004] Regarding the storage of CO2 after capture, "mineralization" technology (converting CO2 into carbonate minerals) is the safest and most reliable solution in the long run. However, its biggest problem is that the cost of raw materials and energy consumption for mineralization remains high. The current cost of mineralization is 50 to 100 times that of geological storage solutions.

[0005] Chinese patent document CN108525637B discloses a carbon template modified calcium-based carbon dioxide adsorbent and its preparation method, the basic operation of which is: mixing an inorganic calcium source (calcium nitrate, etc.) and an inert carrier precursor (magnesium nitrate, etc.) with a carbon source (glucose, etc.) with water, drying, carbonizing at 500°C to 700°C, and calcining at 800°C to obtain a modified calcium-based carbon dioxide adsorbent. The maximum carbon dioxide adsorption capacity is 0.7 to 0.8 gCO2 / g. The preparation procedure of the adsorbent is cumbersome, and the raw material and process energy consumption costs are high.

[0006] Patent document CN201611019756.6 discloses a method for mineralizing carbon dioxide using potassium feldspar sub-molten salt method to produce waste residue. The basic principle is: first, CaO and NaOH or KOH with a mass fraction of 40%-80% are used to leach and extract K from potassium feldspar, and the obtained calcium silicate slag with pseudo-wollastonite (Ca3SiO9) and calcium feldspar (CaAl2Si2O8) as the main phases is used as a carbon dioxide mineralizer; then the obtained mineralizer is mixed with water (solid-liquid ratio 1:1-1:100) and placed in a reactor, CO2 gas (mass fraction greater than 50%, CO2 partial pressure greater than 0.3MPa) is introduced, and stirred (200-800r / min) at a temperature of 30-400℃ for 1-4 hours. Under optimal conditions, the CO2 mineralization efficiency can reach 39% to 46%. The raw materials (potassium feldspar, high-concentration alkali solution) of this method are costly, the concentration of CO2 is required to be high, and the mineralization conditions are harsh, which is not conducive to large-scale deployment. Summary of the invention

[0007] The present invention provides a carbon dioxide adsorption mineralization material and a preparation method and application thereof. The carbon dioxide adsorption mineralization material is prepared based on the method of the present invention, the preparation process is simple, the cost is low, and the obtained material integrates carbon dioxide adsorption and mineralization functions, and can achieve carbon dioxide adsorption and mineralization without harsh conditions; in addition, applying it to the soil where crops grow can also simultaneously fix carbon in the crops and promote crop yield.

[0008] To achieve the purpose, the present invention provides the following technical solutions:

[0009] The first aspect of the present invention provides a method for preparing a carbon dioxide adsorption mineralization material, which mainly comprises the following steps: subjecting a first material and a second material to a hydrothermal reaction at 90-120° C. in an alkaline environment, filtering, washing, and optionally drying the obtained product to obtain a carbon dioxide adsorption mineralization material;

[0010] Wherein, the first material is a silicon source, and the second material is a calcium source; the first material and the second material are fed according to a molar ratio of Si:Ca of 1:0.6-1.5.

[0011] The present invention hydrothermally reacts silicon source and calcium source at 90-120°C in an alkaline environment according to a specific feed ratio, and can obtain a material that integrates carbon dioxide adsorption and mineralization. The material can be used for the capture and mineralization of carbon dioxide, and can achieve the capture and mineralization effects of carbon dioxide without the need for additional concentration and pressure control of carbon dioxide. It can be suitable for directly capturing carbon dioxide from the air under natural conditions and mineralizing it. The present invention obtains carbon dioxide adsorption and mineralization materials through a one-step reaction, and the preparation process is simple, easy to control, and the preparation cost is low. The inventors have found that in the reaction system of the present invention, the reaction temperature is controlled at 90-120°C, and a material with excellent carbon dioxide adsorption and mineralization properties can be obtained. If the temperature is too low or too high, a material with ideal performance cannot be obtained.

[0012] In a preferred embodiment, the first material and the second material are fed according to a Si:Ca molar ratio of 1:0.6 to 1.3, and more preferably a Si:Ca molar ratio of 1:0.6 to 1.2. The adsorption mineralization material obtained by feeding with the preferred molar ratio has a further improved total carbon fixation capacity, and at the same time has good inorganic mineralization carbon fixation capacity and crop carbon fixation capacity.

[0013] In some embodiments, before the hydrothermal reaction, the first material, the second material and the alkaline material are mixed with water to form a mixture, and the concentration of the alkaline agent in the alkaline material in the mixture is 1 to 10 mol / L. In some embodiments, the alkaline agent is selected from NaOH and / or KOH; the alkaline material is an alkaline agent or an aqueous solution of an alkaline agent, that is, the alkaline material can be added in the form of a solid alkaline agent powder or an alkaline agent solution.

[0014] Preferably, the total amount of the first material and the second material in the mixed material has a concentration of 80-250 g / .

[0015] In the preparation method of the present invention, the silicon source can be a liquid silicon source or a solid silicon source, or a mixture of a liquid silicon source and a solid silicon source in any proportion; the calcium source can be a liquid calcium source or a solid calcium source, or a mixture of a liquid calcium source and a solid calcium source in any proportion. In some embodiments, the silicon source includes but is not limited to one or more of Na2SiO3, K2SiO3, water glass, fly ash, silicon-containing smelting slag, silica sol, silica gel, silicon powder, diatomaceous earth, and kaolin. In some embodiments, the calcium source includes but is not limited to one or more of calcium oxide, calcium hydroxide, carbide slag, calcium chloride, calcium sulfate, desulfurized gypsum, phosphogypsum, citric acid gypsum, and calcium nitrate.

[0016] As mentioned above, "the first material and the second material are fed according to a Si:Ca molar ratio of 1:0.6-1.5". If both the first material and the second material contain silicon, then the Si in the molar ratio here is calculated based on the total amount of silicon contained in the first material and the second material; if both the first material and the second material contain calcium, then the Ca here is calculated based on the total amount of calcium contained in the first material and the second material.

[0017] In the preparation method of the present invention, the first material and the second material are subjected to a hydrothermal reaction at 90-120° C. in an alkaline environment, and the hydrothermal reaction time is, for example, 3-5 hours. After the reaction is completed, the mixture is filtered and washed with water, preferably until the pH of the filtrate (the filtrate filtered out during the washing process) is ≤11. The heating, stirring, filtering, washing, drying, etc. involved or possibly involved in the preparation process are all conventional operations in the art. During the preparation process, contact with a gas containing carbon dioxide (such as air) should be reduced as much as possible to reduce the premature reaction of the carbon dioxide adsorption mineralized material with carbon dioxide.

[0018] The carbon dioxide adsorption mineralization material prepared by the preparation method of the present invention can be dried or not according to the use requirements, for example, it can be used directly in the form of a wet filter cake, or the filter cake can be prepared into a slurry of a required concentration for use, or it can be dried into a powder for use.

[0019] The present invention also provides a carbon dioxide adsorption mineralization material, which is prepared by the preparation method described above. In some embodiments, the main active ingredient of the carbon dioxide adsorption mineralization material is Ca-O-Si-H (CaO·SiO2·H2O).

[0020] The present invention also provides a method for adsorbing and mineralizing carbon dioxide, which uses the carbon dioxide adsorption mineralization material described above to adsorb and mineralize carbon dioxide. In some embodiments, the adsorption and mineralization are carried out without additional heating and / or additional pressurization, for example, under natural conditions without additional heating and / or pressurization. In some embodiments, the adsorption and mineralization are carried out at room temperature and pressure. In some embodiments, the adsorption and mineralization are carried out under heating and / or pressurization conditions, but heating and / or pressurization are not necessary to achieve the adsorption and mineralization of carbon dioxide. In some embodiments, the adsorption and mineralization are carried out under the autogenous pressure of the heating conditions. In some embodiments, the adsorbed and mineralized carbon dioxide comes from a carbon dioxide gas source of any concentration and / or pressure and / or temperature, and there is no need to perform additional concentration and / or pressure and / or temperature regulation on the carbon dioxide gas source to be adsorbed and mineralized; in some embodiments, the carbon dioxide gas source is, for example, air. In some embodiments, the carbon dioxide adsorption mineralization material is applied to the soil for adsorption and mineralization, and the soil is, for example, but not limited to, farmland soil or reclaimed land or repaired land; the carbon dioxide adsorption mineralization material of the present invention is applied to the soil, and the natural adsorption and natural mineralization process of air-source carbon dioxide is completed with the growth of vegetation and crops. The adsorption and mineralization process does not require mechanical energy or heat energy input, and the adsorption and mineralization costs are minimized. Moreover, the mineralization products are carbonates and amorphous silicon dioxide, and no further regeneration or harmless treatment is required. The mineralization products can also provide effective silicon and other mineral nutrients for crop growth and improve the soil structure function, thereby increasing the amount of crop carbon fixation and increasing the yield of crops. In some embodiments, the carbon dioxide adsorption mineralization material of the present invention performs carbon dioxide adsorption and mineralization treatment, and the mineralization efficiency is high, and the Ca element therein can be almost completely converted into stable calcium carbonate phases such as calcite and vaterite.

[0021] The present invention also provides an application of the carbon dioxide adsorption mineralization material described above, wherein the carbon dioxide adsorption mineralization material is used as a soil conditioner; or, the carbon dioxide adsorption mineralization material is used in a method for promoting crop yield increase; or, the carbon dioxide adsorption mineralization material is used in a method for carbon dioxide adsorption, mineralization, and simultaneous promotion of crop yield increase. Specifically, the carbon dioxide adsorption mineralization material obtained by the present invention is applied to the soil as a soil conditioner, which can provide the soil with mineral nutrients such as effective silicon while completing the natural adsorption and natural mineralization process of air-source carbon dioxide, thereby facilitating soil conditioning and / or repair and promoting crop yield increase. Preferably, the application amount of the carbon dioxide adsorption mineralization material is 600kg to 3000kg / hm 2 .

[0022] The carbon dioxide adsorption mineralization material of the present invention is used in a method for promoting crop yield increase. Specifically, the carbon dioxide adsorption mineralization material described above can be applied to the soil used for crop growth to promote yield increase. Preferably, the amount of carbon dioxide adsorption mineralization material applied is 600kg to 3000kg / hm2. 2 The carbon dioxide adsorption mineralization material of the present invention is applied to the soil to complete the natural adsorption and natural mineralization process of air-source carbon dioxide along with the growth of crops. At the same time, the mineralization product also provides effective silicon and other mineral nutrients for crop growth, which can achieve a good yield-increasing effect.

[0023] The carbon dioxide adsorption mineralization material of the present invention is used in the method of carbon dioxide adsorption, mineralization and simultaneous promotion of crop yield increase. Specifically, the carbon dioxide adsorption mineralization material can be applied to the soil for crop growth; preferably, the application amount of the carbon dioxide adsorption mineralization material is 600kg to 3000kg / hm 2 Applying the carbon dioxide adsorption mineralization material of the present invention to the soil can achieve the natural adsorption and natural mineralization of air-source carbon dioxide, and simultaneously achieve a good crop yield increase effect.

[0024] The technical solution provided by the present invention has the following beneficial effects:

[0025] The preparation method of the carbon dioxide adsorption mineralizer provided by the present invention can prepare a carbon dioxide adsorption mineralizer with excellent performance by a simple process, and the preparation energy consumption is low and the cost is low. The obtained carbon dioxide adsorption mineralizer has no strict conditions for the adsorption and mineralization of carbon dioxide, can adsorb and mineralize carbon dioxide from air sources under natural conditions, and can be used as a soil conditioner or a crop yield promoter. While adsorbing and mineralizing carbon dioxide, it provides mineral nutrients for crops, and simultaneously has a good yield-increasing effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the XRD analysis result of the adsorption mineralizer prepared in Example 1.

[0027] Figure 2 This is the XRD analysis result of the carbon dioxide adsorption mineralization product in Example 1. DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0029] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0030] In the following examples or comparative examples, the carbon fixation capacity of the adsorption mineralizer is calculated as follows:

[0031] A: For centralized carbon capture and mineralization (e.g., Examples 1-3, 7)

[0032] After the adsorption mineralizer is subjected to carbon dioxide adsorption and mineralization treatment, it is dried (if the adsorption mineralizer is used in the form of slurry, the filter cake is dried after filtration), and XRD analysis (X-ray diffraction analysis) is performed to confirm the conversion rate (or mineralization rate) of the Ca element into the calcium carbonate phase.

[0033] The inorganic mineralization carbon fixation capacity Q=Qa per ton of adsorption mineralizer is calculated according to the following calculation formula (I):

[0034] Q a =M*q*12 / 1000

[0035] Among them, Q a is the inorganic mineralization carbon fixation capacity per ton of adsorption mineralizer, kgC*t -1 ;

[0036] M is the amount of CaO in each ton of adsorbed mineralizer, mol;

[0037] q is the mineralization rate, which means the mass ratio of CaO converted to CaCO3 in the mineralized product, which is calculated by XRD quantitative software, %;

[0038] 12 is the molecular weight of C.

[0039] B: For distributed carbon capture and mineralization combined with crop carbon sequestration (e.g., Examples 4-6, 8-10), the total carbon sequestration capacity Q per ton of adsorbed mineralizer is calculated using formula (II):

[0040] Q=Q b+ Qc=N Ca *0.214*1000+1 / A*j*k

[0041] Among them, Q b and Qc are the inorganic mineralization carbon fixation capacity and crop carbon fixation capacity per ton of adsorbed mineralizer under natural field conditions, kgC*t -1 ;

[0042] N Cais the mass percentage of effective calcium in the carbon dioxide adsorption mineralizer, %; specifically, N Ca The meaning is: the mass percentage of calcium (calculated as CaO) in the sample that can react with weakly acidic substances in the soil to the total weight of the sample. The determination method of effective calcium is carried out in accordance with the standard NYT 2272-2012 "Determination of calcium, magnesium and silicon content of soil conditioners" (the inventor found in the research process that the effective calcium data measured in accordance with the above standard can basically 100% indicate the actual CO2 mineralization and fixation capacity of the sample).

[0043] 0.241 is the mass conversion factor of C that can be mineralized and fixed by effective calcium;

[0044] A is the mass of adsorbed mineralizer or soil conditioner applied per hectare of farmland, t*hm -2 ;

[0045] j is the carbon sequestration capacity of crops, kgC·hm -2 ; The carbon sequestration capacity of different types of crops in different regions can be found in the table below. For example, the carbon sequestration capacity of rice in South China is about 2573 kgC·hm -2 ;

[0046] k is the increase rate of crop carbon fixation capacity after applying carbon dioxide adsorption mineralizer in the soil (%), which is approximately equal to the increase rate of crop aboveground biomass (%) (when calculating, the increase rate of crop aboveground biomass is taken as the value of k), which is actually measured by field experiments. The calculation formula of the growth rate is:

[0047] k=Tx / CK*100%-100%

[0048] Where Tx represents the aboveground biomass yield per unit area of ​​the crop in the treatment group (where adsorbed mineralizer was applied as soil conditioner), t / hm 2 ;

[0049] CK represents the aboveground biomass yield per unit area of ​​the blank control group (the only difference from the treatment group is that the above-mentioned adsorbed mineralizer is not applied), t / hm 2 .

[0050] Table 1 Net carbon content of crop production in each region and its components (kgC·hm -2 )

[0051]

[0052] *Table 1 is from the following literature: She Wei, Huang Huang, Guan Chunyun, et al. Current status and optimization approaches of carbon sink structure of major crop production in my country[J]. China Engineering Science, 2016, 18(1):9.

[0053] Example 1

[0054] (1) Preparation of carbon dioxide adsorption mineralizer

[0055] Fly ash is used as the first material, and carbide slag is used as the second material.

[0056] The carbon dioxide adsorption mineralizer was prepared according to the following steps:

[0057] 1) fly ash with a silicon dioxide content of 64 wt% and carbide slag (effective component Ca(OH)2) are uniformly mixed at a molar ratio of Si:Ca=1:0.6 to obtain a mixture I;

[0058] 2) adding solid NaOH powder to mixture I, and adding water to prepare mixture II, so that the concentration of NaOH in mixture II is 2.0 mol / L, and the concentration of mixture I in mixture II is 80 g / L;

[0059] 3) Stirring and heating the mixture II to 100°C, and keeping the temperature to react for 4 hours;

[0060] 4) After the reaction is completed, the reaction is performed and the filter cake is then washed with water until the pH of the filtrate is ≤11, thereby obtaining a carbon dioxide adsorption mineralizer; the carbon dioxide adsorption mineralizer is subjected to XRD analysis, and its XRD spectrum is shown in Figure 1 shown.

[0061] (2) Adsorption and mineralization of carbon dioxide

[0062] Take the wet cake of carbon dioxide adsorption mineralizer with a dry weight of 1 ton obtained in (1), add water to make a slurry with a solid content of 30%, and continuously blow air (CO2 gas source) into the slurry at room temperature and pressure to carry out direct air capture and storage (DACCS) reaction of carbon dioxide. After blowing air for about 4 hours, the CO2 concentration in the outlet gas path no longer changes, and the reaction is completed. Filter to separate the solid and liquid, take the filter cake and dry it, and then test the carbon fixation capacity Q of the adsorption mineralizer. The carbon dioxide adsorption mineralization reaction product is analyzed by XRD ( Figure 2 ), except for the CaCO3 phase, there is no other calcium-containing phase, and the conversion rate (or mineralization rate) of Ca is q = 100%. The data are shown in Table 2.

[0063] Example 2

[0064] The process was carried out with reference to Example 1, except that the adsorption and mineralization process of carbon dioxide in Example 1 was changed from a normal temperature and pressure environment to an autogenous pressure of 100°C. According to XRD analysis, except for the CaCO3 phase, no other calcium-containing phase existed, and the conversion rate (or mineralization rate) of CaO was q=100%. The carbon fixation capacity Q data of the adsorption mineralizer in this example are shown in Table 2.

[0065] Example 3

[0066] The method was carried out in accordance with Example 1, except that the wet cake of carbon dioxide adsorption mineralizer in Example 1 was left open and placed in the air at normal pressure and temperature for 14 days to carry out DACCS reaction. After the reaction, a sample of the solid reaction product was taken and dried to test the carbon fixation capacity Q of the adsorption mineralizer. The carbon dioxide adsorption mineralization reaction product was analyzed by XRD, and the results showed that except for the CaCO3 phase, there was no other calcium-containing phase, and the conversion rate (or mineralization rate) of Ca was q=100%. The data are shown in Table 2.

[0067] Example 3 shows that the use of the carbon dioxide adsorption mineralizer in the present invention can achieve spontaneous adsorption and mineralization reaction of carbon dioxide in the air under natural temperature, pressure and the presence of water; by appropriately extending the reaction time (14d), the adsorption mineralization reaction can be carried out thoroughly.

[0068] Example 4

[0069] The carbon dioxide adsorption mineralizer wet cake obtained in Example 1 was dried and applied as a soil conditioner to the rice test field in Xinyi, Jiangsu Province, with a dosage of 2400 kg (dry weight) per hectare, and a blank control group was set up. After the rice matured, the aboveground biomass of the crop was harvested and tested, which was the yield measurement. It can be seen from Table 1 that the carbon fixation capacity of rice crops in this area is 2573 kgC / hm 2 The yield measurement results showed that the above-mentioned carbon dioxide adsorption mineralizer (i.e. soil conditioner) increased the aboveground biomass of crops by 25.0% compared with the blank control group. Therefore, it can be considered that the increase in crop carbon fixation capacity due to the increase in biomass is also 25%. b and crop carbon sequestration Q c The two parts of data are used to calculate the total carbon fixation capacity Q. Refer to the calculation formula (II) above and the results are shown in Table 2.

[0070] Example 5

[0071] Only the dosage of the carbon dioxide adsorption mineralizer (i.e., soil conditioner) in Example 4 was adjusted to 1200 kg (dry weight) per hectare. The aboveground biomass yield of crops in this example increased by 19.2%. The total carbon fixation capacity Q is shown in Table 2.

[0072] Example 6

[0073] Only the dosage of the carbon dioxide adsorption mineralizer (i.e., soil conditioner) in Example 4 was adjusted to 600 kg (dry weight) per hectare. The aboveground biomass yield increase rate of the crop in this example was 9.0%. The total carbon fixation capacity Q is shown in Table 2.

[0074] Example 7

[0075] The carbon dioxide adsorption mineralizer was prepared by referring to the preparation steps of Example 1, except that the fly ash in Example 1 was replaced by water glass (Na2SiO3·nH2O); the calcium carbide slag was replaced by desulfurized gypsum (CaSO4·2H2O), and the amounts of water glass and desulfurized gypsum were determined according to the molar ratio of Si:Ca=1:1.2.

[0076] The measured mineralization carbon fixation capacity Qa is shown in Table 2.

[0077] Example 8

[0078] The carbon dioxide adsorption mineralizer was prepared by referring to the preparation steps of Example 1, except that the fly ash in Example 1 was replaced by water glass (Na2SiO3·nH2O); the calcium carbide slag was replaced by desulfurized gypsum (CaSO4·2H2O), and the amounts of water glass and desulfurized gypsum were determined according to the molar ratio of Si:Ca=1:0.8.

[0079] The obtained carbon dioxide adsorption mineralizer was applied to the paddy field as a soil conditioner according to Example 4. b and crop carbon sequestration capacity Q c The total carbon fixation capacity Q is calculated based on the two parts of data, as shown in Table 2.

[0080] Example 9

[0081] The carbon dioxide adsorption mineralizer was prepared by referring to the preparation steps of Example 1, except that fly ash and carbide slag were added according to the molar ratio of Si:Ca = 1:1.0, the NaOH concentration was 10 mol / L, the reaction temperature was 90°C, and the insulation reaction time was 5 h.

[0082] The obtained carbon dioxide adsorption mineralizer was applied to the paddy field as a soil conditioner according to Example 5. The results of carbon fixation capacity Q are shown in Table 2.

[0083] Example 10

[0084] The carbon dioxide adsorption mineralizer was prepared by referring to the preparation steps of Example 1, except that fly ash and carbide slag were fed according to the molar ratio of Si:Ca = 1:1.2, the NaOH concentration was 5 mol / L, the reaction temperature was 120°C and autogenous pressure, and the synthesis time was 3 h.

[0085] The obtained carbon dioxide adsorption mineralizer was applied to the paddy field as a soil conditioner according to Example 6. The results of carbon fixation capacity Q are shown in Table 2.

[0086] Comparative Example 1

[0087] This comparative example is carried out with reference to Example 9, except that: when preparing the carbon dioxide adsorption mineralizer, fly ash and carbide slag are added according to the molar ratio of Si:Ca=1:1.5, and the other conditions remain unchanged.

[0088] The results of carbon fixation capacity Q are shown in Table 2.

[0089] From the experimental results, it can be seen that compared with Example 9, after the molar ratio of calcium to silicon in the raw material is increased, the inorganic mineralization and carbon fixation capacity of the adsorbed mineralizer is slightly improved, but after application to field soil, the crop yield decreases by 5%, and the increase in the crop carbon fixation capacity is negative, resulting in a decrease in the total carbon fixation capacity.

[0090] Comparative Example 2

[0091] This comparative example was carried out with reference to Example 5, except that: when preparing the carbon dioxide adsorption mineralizer, fly ash and carbide slag were added according to the molar ratio of Si:Ca = 1:0.4, and the other conditions remained unchanged. The results of the carbon fixation capacity Q are shown in Table 2.

[0092] From the experimental results, it can be seen that compared with Example 5, after the raw material calcium-silicon molar ratio is lowered, the inorganic mineralization carbon fixation capacity of the adsorbed mineralizer is significantly reduced, and the crop yield increase rate is only 8%, and the yield increase effect is not significant. Both the mineralization carbon fixation capacity and the crop carbon fixation capacity are reduced, resulting in a significant decrease in the total carbon fixation capacity.

[0093] Comparative Example 3

[0094] The method is carried out in accordance with Example 3, except that, when preparing the carbon dioxide adsorption mineralizer, fly ash and carbide slag are fed according to the molar ratio of Si:Ca = 1:1.5. It is generally believed that a higher Ca content can improve the theoretical carbon fixation capacity of the carbon dioxide adsorption mineralizer (theoretical value 87.9 kgC*t -1 ); however, the XRD analysis results of the reaction products show that in addition to the CaCO3 phase, a large amount of Ca(OH)2 phase remains in the carbon dioxide adsorption mineralization product. This shows that when Ca is added in excess, the carbon dioxide adsorption and mineralization reaction cannot be completely carried out even after 14 days under natural temperature, pressure and water conditions. The conversion rate (or mineralization rate) of Ca was measured to be only q=67.1%, and its actual mineralization carbon fixation capacity was calculated to be only Q=59kgC*t -1 (See Table 2); Although numerically better than Example 3, the utilization rate of Ca is low, resulting in a significantly higher cost of preparing the mineralizer than that of Example 3, and the composition of the mineralized product is more complex than that of Example 3 (containing residual Ca(OH)2), which is not conducive to further disposal or utilization of the mineralized product.

[0095] Table 2 Carbon fixation capacity of 1 ton of carbon dioxide adsorption mineralizer

[0096]

[0097]

[0098] As can be seen from the above experimental results, the preparation process of the adsorption mineralizer provided by the present invention is simple and low in cost. The preparation cost can be controlled at about 400 yuan / t after calculation, which is significantly lower than the conventional organic amine carbon dioxide adsorbent, and this part of the cost can also be completely offset by the increase in crop production and income, so the overall carbon fixation cost of the carbon dioxide adsorption and mineralization process combined with crop carbon fixation is negative. This is an advantage that the existing CCS or DACCS technology does not have. In addition, the adsorption mineralizer of the present invention can adsorb and mineralize carbon dioxide at room temperature and pressure, and it can adsorb and mineralize carbon dioxide from the air, which is conducive to flexible deployment and low requirements for mineralization conditions; and the mineralized product after the adsorption mineralizer of the present invention performs carbon dioxide adsorption and mineralization is harmless to the environment and can promote crop yield increase; however, traditional mineralization technology cannot be carried out at room temperature and pressure, and its high temperature and high pressure mineralization product needs further harmless disposal.

[0099] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A method for preparing a carbon dioxide adsorption mineralization material, characterized in that: The steps include: The first material and the second material are subjected to a hydrothermal reaction at 90-120° C. in an alkaline environment, and the obtained product is filtered, washed, and optionally dried to obtain the carbon dioxide adsorption mineralization material; The first material is a silicon source, and the second material is a calcium source; the first material and the second material are fed according to a molar ratio of Si:Ca of 1:0.6-1.

5.

2. The preparation method according to claim 1, characterized in that: The molar ratio of Si:Ca is 1:0.6-1.3, preferably 1:0.6-1.

2.

3. The preparation method according to claim 1, characterized in that: Before the hydrothermal reaction, the first material, the second material and the alkaline material are mixed with water to form a mixture, wherein the concentration of the alkaline agent in the alkaline material in the mixture is 1 to 10 mol / L; Preferably, the total amount of the first material and the second material in the mixture has a concentration of 80-250 g / L; Preferably, the alkaline agent is selected from NaOH and / or KOH; the alkaline material is an alkaline agent or an aqueous solution of an alkaline agent.

4. The preparation method according to any one of claims 1 to 3, characterized in that The silicon source is a liquid silicon source or a solid silicon source, or a mixture of a liquid silicon source and a solid silicon source; The calcium source is a liquid calcium source or a solid calcium source, or a mixture of a liquid calcium source and a solid calcium source; Preferably, the silicon source includes one or more of Na2SiO3, K2SiO3, water glass, fly ash, silicon-containing smelting slag, silica sol, silica gel, silica powder, diatomaceous earth, and kaolin; Preferably, the calcium source includes one or more of calcium oxide, calcium hydroxide, carbide slag, calcium chloride, calcium sulfate, desulfurized gypsum, phosphogypsum, limonite, and calcium nitrate.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The hydrothermal reaction time is 3-5h; Preferably, the washing is performed until the pH of the filtrate is ≤11.

6. A carbon dioxide adsorption mineralization material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 5.

7. A method for adsorbing and mineralizing carbon dioxide, characterized in that: Adsorbing and mineralizing the carbon dioxide using the carbon dioxide adsorption mineralization material according to claim 6; Preferably, the adsorption and mineralization are carried out without additional heating and / or additional pressurization; or, the adsorption and mineralization are carried out under heating and / or pressurization; or, the adsorption and mineralization are carried out under autogenous pressure under heating conditions; Further preferably, the adsorption and mineralization are carried out at normal temperature and pressure.

8. The method according to claim 7, characterized in that The gas source containing carbon dioxide to be treated is not subjected to additional concentration and / or pressure and / or temperature regulation before contacting the carbon dioxide adsorbing mineralization material. The carbon dioxide gas source is, for example, air.

9. The method according to claim 7, characterized in that: The carbon dioxide adsorption and mineralization material is applied to soil for the adsorption and mineralization.

10. The use of the carbon dioxide adsorption mineralization material according to claim 6, characterized in that: The carbon dioxide adsorption mineralization material is used as a soil conditioner; Alternatively, the carbon dioxide adsorption mineralization material is used in a method for promoting crop yield increase. Preferably, the carbon dioxide adsorption mineralization material is applied to soil for crop growth. Further preferably, the amount of carbon dioxide adsorption mineralization material applied is 600kg to 3000kg / hm 2 ; Alternatively, the carbon dioxide adsorption mineralization material is used in a method for carbon dioxide adsorption, mineralization and simultaneous promotion of crop yield increase, and the carbon dioxide adsorption mineralization material is applied to soil for crop growth; preferably, the application amount of the carbon dioxide adsorption mineralization material is 600kg to 3000kg / hm 2 .

Citation Information

Patent Citations

  • A method for carbon dioxide mineralization using waste residues produced by the sub-molten salt method of potassium feldspar

    CN106629802B

  • A carbon template-modified calcium-based carbon dioxide adsorbent and its preparation method

    CN108525637B